2020
DOI: 10.1177/0145721720964585
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Gender Differences in the National Diabetes Prevention Program’s Lifestyle Change Program

Abstract: Purpose The purpose of the study was to examine how gender was related to enrollment and number of sessions attended in the National Diabetes Prevention Program’s Lifestyle Change Program (DPP LCP). Methods To better understand program uptake, a population of those who would be eligible for the LCP was compared to those who enrolled. Estimates of those eligible were computed using data from the National Health and Nutrition Examination Survey, whereas enrollment and sessions attended were computed using data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…One of these studies compared population estimates of eligibility to actual enrollment and found that adults who were eligible, but did not enroll in the National DPP during the first 5 years of its nationwide implementation were more likely to be younger or older (relative to middle aged), Hispanic (relative to non-Hispanic), and male (relative to female). 16 Over this same time frame, individuals who enrolled inbut did not completethe National DPP were more likely to be younger and racial/ethnic minority participants. 19 Qualitative studies have identified barriers to enrollment and retention, including childcare, transportation, and scheduling, 10 , 15 length of the year-long program, and discomfort with the group modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these studies compared population estimates of eligibility to actual enrollment and found that adults who were eligible, but did not enroll in the National DPP during the first 5 years of its nationwide implementation were more likely to be younger or older (relative to middle aged), Hispanic (relative to non-Hispanic), and male (relative to female). 16 Over this same time frame, individuals who enrolled inbut did not completethe National DPP were more likely to be younger and racial/ethnic minority participants. 19 Qualitative studies have identified barriers to enrollment and retention, including childcare, transportation, and scheduling, 10 , 15 length of the year-long program, and discomfort with the group modality.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Just one known study of the National DPP, focused on women of childbearing age, includes in-depth interviews with patients from within a health system. 15 Given women's higher engagement with the National DPP to date, 16 there is substantial opportunity for qualitative study in this group. This study extends the research with a qualitative analysis of barriers and facilitators to enrollment and retention within a health system from the perspectives of (1) women referred to the National DPP and (2) referring clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Although equivalent weight loss yielded greater reduction in risk factors for type 2 diabetes for men than their women counterparts, 27 women are over three times as likely to enroll in the NDPP lifestyle change program. 28 In the DPP Outcomes Study, coronary calcium score severity was less in men receiving metformin versus placebo, an effect not seen in women. 29 In a meta-analysis, no sex-specific differences in the reduction in incidence of type 2 diabetes was appreciated in both lifestyle and pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although some older participants may be reluctant to adopt new technologies, virtual delivery approaches have shown promise with this age group [ 24 ]. Online organizations enrolled a somewhat higher proportion of men than in-person organizations and thus may be an important avenue for increasing the relatively low proportion of men who enroll in the National DPP lifestyle change program [ 13 ]. The organizations with no in-person component (i.e., online and distance learning) enrolled lower proportions of participants who were Hispanic/Latino or non-White, suggesting that in order to reduce health disparities, these delivery modes need to be made more accessible and appealing to minority racial and ethnic groups [ 25 ].…”
Section: Discussionmentioning
confidence: 99%